Pathobiological analysis of African swine fever virus contact-exposed pigs and estimation of the basic reproduction number of the virus in Vietnam - Sang-Ik Oh; Ngoc Anh Bui; Vuong Nghia Bui; Duy Tung Dao; Ara Cho; Han Gyu Lee; Young-Hun Jung; Yoon Jung Do; Eunju Kim; Eun-Yeong Bok; Tai-Young Hur; Hu Suk Lee (Springer, 2023)
Background African swine fever (ASF), caused by African swine fever virus (ASFV), is a fatal disease affecting wild and domestic pigs. Since China reported the first ASF outbreak in August 2018, ASFV has swept over the neighbouring Asian countries. However, studies involving experimental pig-to-pig ASFV transmission in Vietnam are lacking. The main objective of this experimental study was to demonstrate the pathobiological characteristics of ASFV contact-exposed pigs and estimate their basic reproduction number (R0) in Vietnam. Fifteen pigs were randomly divided into two groups: experimental (n = 10) and negative control (n = 5) groups. One pig in the experimental group was intramuscularly inoculated with ASFV strain from Vietnam in 2020 and housed with the uninoculated pigs during the study period (28 days).